„Intermedijalna osjetljivost” poezije Antuna Gustava Matoša, perspektiva lirskog subjekta - Jukić, Sanja (Poznańskie Studia Slawistyczne, 2014)
The paper aims to show that the lyrical subject of Matošʼs poetry is indeed a media hybrid structure. This subject usually identifies with the signifiers of other artistic media, such as the theater, dance, music, painting, fashion and architecture. Therefor, Matoš’s lyrical subject reveals itself as a media hybrid being, which is defined by both time and culture.